Inverse displacement analysis of a hyper-redundant bionic trunk-like robot. (13th February 2020) - Zhao, Yongjie; Zhang, Yongxing; Li, Jianyuan; Jin, Lei; He, Jun; Zhang, Xingwei; Lu, Xinjian
This article presents the inverse displacement analysis of a hyper-redundant bionic trunk-like robot. The hyper-redundant bionic trunk-like robot is constituted of some parallel mechanism modules in series. The mathematical model of the inverse displacement analysis of the hyper-redundant robot comprises a set of nonlinear consistent equations with a number of unknown variables that are more than given equations. It is impossible to find all solutions for the inverse displacement analysis since there are infinite solution possibilities. By planning the pose of distal moving platforms for robot modules, the problem of the inverse displacement analysis of the hyper-redundant robot is transformed into that of a parallel mechanism. The inverse velocity and acceleration computation are then implemented using a method of the numerical differentiation. A developed prototype of a hyper-redundant bionic trunk-like robot is presented. The approach can be applied to the hyper-redundant robot with man–machine interactive system in the unstructured environment.